1989
DOI: 10.1182/blood.v74.5.1472.1472
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and granulocyte-macrophage colony-stimulating factor are candidate growth factors for chronic myelomonocytic leukemia cells

Abstract: Previous studies suggest that malignant cells from some patients with myeloid leukemias produce colony-stimulating factors (CSFs) that can function as autocrine growth factors in vitro. We have examined the roles of interleukin-6 (IL-6) and granulocyte-macrophage CSF (GM-CSF) in the proliferation of myeloid leukemia cells. IL-6 activity was assessed in conditioned medium (CM) from myeloid leukemia cell cultures or cell lysates using IL-6-dependent KD83 and 7TD1 murine cell lines. Media conditioned by cells fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It is generally assumed that the constitutive tyrosine kinase activity of BCR-ABL oncoprotein promotes CML cell growth and cell survival leading to relative cytokine independence 59 . Conversely, several cytokines have been reported to expand primitive CML cells including IL-6 [60][61][62][63] . IL-6 is highly expressed in CML patients 64 and its expression is associated with poor prognosis 65,66 .…”
Section: Discussionmentioning
confidence: 99%
“…It is generally assumed that the constitutive tyrosine kinase activity of BCR-ABL oncoprotein promotes CML cell growth and cell survival leading to relative cytokine independence 59 . Conversely, several cytokines have been reported to expand primitive CML cells including IL-6 [60][61][62][63] . IL-6 is highly expressed in CML patients 64 and its expression is associated with poor prognosis 65,66 .…”
Section: Discussionmentioning
confidence: 99%
“…There is clear evidence in the literature that IL‑6 is one of the main stimulatory factors of IgG production [ 28 , 29 ]. On the other hand, it has been shown that CMML cells can produce IL‑6 in vitro and stimulate CMML cell growth in an autocrine manner [ 30 ]. One attractive hypothesis of our exploratory findings could be that IL‑6 may provide a common basis for hypergammaglobulinemia and the adverse outcome in these patients.…”
Section: Discussionmentioning
confidence: 99%